Developing Globally-Competent University Teachers - Badley, Graham (Innovations in education and teaching international, 2000)
What is global competence in university teaching? And, assuming we can provide some sort of reasonable answer to that first question, how might it be developed? What is argued within this paper is that the traditional university assumption that subject experts (with no - or scarcely any - pedagogic training) make fit teachers is even less justifiable when these teachers travel abroad to teach overseas students than when they operate in their home university with students who, for the most part, share many of their own socio-cultural values and beliefs. Given that higher education teachers in the UK will soon be expected (though not required) to seek membership of the Institute of Learning and Teaching (ILT) based either on their completion of an accredited training programme or on their submission of a portfolio evidencing their practical competence in teaching there is therefore a national, systemic, move towards pedagogic training. However it is argued further that, though necessary and desirable for all university teachers wherever they are teaching, academic subject knowledge and accredited pedagogic skills are still insufficient for those wishing to be regarded internationally as globally competent teachers. Two further requirements are both necessary and desirable for global competence in teaching: the adoption of a transformatory and democratic approach to education and the development of what may be termed an ethnographic stance to teaching abroad.